Free amino acids hydroxyproline, lysine, and glycine promote differentiation of retinal pericytes to adipocytes: A protective role against proliferative diabetic retinopathy. (August 2018) - Vidhya, S.; Ramya, R.; Coral, K.; Sulochana, K.N.; Bharathidevi, S.R.
Abstract: Aim: This study was conducted to estimate the aminoacid levels in the vitreous of patients with proliferative diabetic retinopathy, and to correlate it with the adiponectin levels. Secondly to test if these amino acids can alter or induce adiponectin levels and its related factors in retinal cells like pericyte as an in vitro model. Methods: All human studies were done as per declaration of Helsinki with institutional approval and after obtaining consent from participating individuals. The vitreous amino acids were estimated in PDR (Proliferative diabetic retinopathy) and MH (Macular Hole) as disease control using HPLC. Bovine retinal pericytes (BRP) were cultured in DMEM/F12 medium and treated with 0.5 mM of any one of the individual amino acids (proline, hydroxyproline, phenylalanine, alanine, serine, glycine, lysine, isoleucine or valine) along with 100 nM insulin for 14 days in high glucose (25 mM) condition. The mRNA expression profile of adipogenic markers (such as Pref1, APN, ZAG and PPARγ), angiogenic markers (VEGF, MMP-2 and MMP-9, TGF-β) and antioxidant markers (Nrf2 and UCP-2) were evaluated by qPCR. Adipogenesis was further confirmed by adipogenesis assay, secretion of adiponectin in medium and triglyceride accumulation by Oil red O staining in Bovine retinal pericytes. Results: Amino acids valine (p < 0.004), isoleucine (p < 0.0007), leucine (p < 0.022), serine (p < 0.0007), glycine (p < 0.001), alanine (p < 0.017), phenylalanine (p < 0.013), and lysine (p < 0.001) were significantly elevated in the vitreous of PDR group (n = 30) when compared to macular hole (n = 20). There was a significant positive correlation between serine (p < 0.021), alanine (p < 0.00016), phenylalanine (p < 0.04), isoleucine (p < 0.023), leucine (p < 0.043), and lysine (p < 0.026) with adiponectin level in the vitreous. The amino acids hydroxyproline, proline, lysine, glycine and alanine induced the triglyceride accumulation and expression of Adiponectin. VEGF and MMP-9 expression was decreased with all the amino acids treated and PEDF was significantly increased with phenylalanine treatment. TGFβ mRNA expression showed a significant decrease with proline, alanine, glycine, lysine and isoleucine. The Nrf2 expression was significantly increased in alanine and serine when compared to control. The UCP-2 gene showed a significant increase in proline and lysine treatment. Discussion and conclusion: Our results suggest that amino acids hydroxyproline, proline, lysine, glycine and alanine which are elevated in the PDR vitreous show a tendency to induce adipogenic effects in retinal pericytes by triggering the accumulation of triglycerides and adiponectin. Hence we hypothesize that these aminoacids when elevated along with insulin and glucose can induce metabolic changes in pericytes. The functional implications of these changes tend to be protective as it increases the antioxidant potential and decreases the angiogenesis markers which are potentially pathogenic. Highlights: Serine, glycine, alanine and phenylalanine along with branched chain amino acids increased in PDR vitreous. These amino acids significantly down regulated VEGF and MMP 9 mRNA expression in retinal pericytes. Hydroxyproline, glycine and lysine have a greater effect on pericytes towards differentiation to adipocytes. Glycine other than being adipogenic was found to increase NRF2 and decrease UCP2 and TGF-β mRNA levels.